Simultaneous effects of single wall carbon nanotube and effective variable viscosity for peristaltic flow through annulus having permeable walls - Shahzadi, Iqra; Nadeem, S.; Rabiei, Faranak (Elsevier, 2017)
The current article deals with the combine effects of single wall carbon nanotubes and effective viscosity for the peristaltic flow of nanofluid through annulus. The nature of the walls is assumed to be permeable. The present theoretical model can be considered as mathematical representation to the motion of conductive physiological fluids in the existence of the endoscope tube which has many biomedical applications such as drug delivery system. The outer tube has a wave of sinusoidal nature that is travelling along its walls while the inner tube is rigid and uniform. Lubrication approach is used for the considered analysis. An empirical relation for the effective variable viscosity of nanofluid is proposed here interestingly. The viscosity of nanofluid is the function of radial distance and the concentration of nanoparticles. Exact solution for the resulting system of equations is displayed for various quantities of interest. The outcomes show that the maximum velocity of SWCNT-blood nanofluid enhances for larger values of viscosity parameter. The pressure gradient in the more extensive part of the annulus is likewise found to increase as a function of variable viscosity parameter. The size of the trapped bolus is also influenced by variable viscosity parameter. The present examination also revealed that the carbon nanotubes have many applications related to biomedicine.